WISDOM VS FOLLY: ON TWO KINDS OF EDUCATION IN HRYHORII SKOVORODA AND ERASMUS OF ROTTERDAM - Tolstov , Ivan; Chernyshov, Victor (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2024)
This paper addresses the issue of education as presented in the works of Erasmus of Rotterdam (c. 1466–1536) and Hryhorii Skovoroda (1722–1794). The study seeks to explore two contrasting approaches to education, with particular emphasis on wisdom and folly as two potential (intentional or unintentional) outcomes of education, which influence the destinies of both individuals and society as a whole. Specifically, it asserts that Erasmus’s works had a profound impact on Skovoroda’s educational views and served as the foundation for the development of several other fundamental ideas reflected in his philosophical writings. The article underscores the importance of education as a means of humanising the individual, cultivating the capacity for free choice, and facilitating socialization. Both Skovoroda and Erasmus concur that education is a necessary condition for the formation of the individual as a person; however, they differ in their assessments of the balance between the secular and spiritual elements within education. Erasmus contended that the education of his time lacked a secular dimension, while Skovoroda, writing some 250 years later, highlighted the absence of a spiritual component, which, in his view, led to spiritual thirst and profound inner turmoil within individuals. In the context of the educational issues of their respective eras, both thinkers critique the societal inclination to favour folly over wisdom. Special attention is devoted to comparing their views on the nature of folly as a source of human suffering and social malaise. The paper aims not only to compare the educational concepts proposed by these two distinguished philosophers but also to provoke reflection on the nature and intentions of education within the Ukrainian educational tradition. The analysis of the ideas of Skovoroda and Erasmus thus offers an opportunity to deepen our understanding of the philosophy of education, as well as to uncover new avenues for the enhancement of contemporary educational systems through the reception of classical humanist values.